Pengaruh Tingkat Inflasi Dan Nilai Tukar Rupiah Terhadap Volume Impor Mobil CBU (Completely Built Up) Di Indonesia - Hawari, Habil Mirza; Fadhila Rahma, Tri Inda; Tambunan, Khairina (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine and analyze the effect of inflation and the rupiah exchange rate on imports of CBU cars in Indonesia.The population in this study is the monthly report on inflation and the monthly report on the rupiah exchange rate and the monthly report on the number of imports of CBU cars in Indonesia in the period 2017-2021.The sample in this study amounted to 60 samples.The Data used in this study are secondary data, namely time-series data and sample selection using saturated sample Method. The Data were analyzed using SPSS version 25.The data analysis is done by classical assumption test and hypothesis test.The results showed that the partial inflation positively and significantly affect the import of CBU cars, and the rupiah exchange rate did not significantly affect the import of CBU cars.Simultaneously (together) there is a positive and significant influence between inflation variables and the rupiah exchange rate on imports of CBU cars in Indonesia.based on the coefficient of determination test, inflation and the rupiah exchange rate have an effect of 46.2 percent on CBU car imports in Indonesia.